Evidence of influenza or influenza-like-illness preceding acute coronary syndrome - Kuanprasert S. (2014)
This observational study determined the prevalence of influenza and influenza-like-illness (ILI) in patients hospitalized for acute coronary syndrome (ACS). Serological confirmation and a clinical history of influenza or a recent acute upper respiratory infection were obtained in 376 patients admitted to Maharaj Nakhon Chiang Mai Hospital, Thailand, from June 2006 through May 2007 for ACS. We found evidence of confirmed influenza preceding ACS in 47 patients (12.5%) and for recent ILI in 41 patients (11 %). There were more influenza and ILI patients admitted in the winter than in other months. Influenza vaccination may be protective in high risk patients.